2021
DOI: 10.1007/s12310-021-09476-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity Among Moderate Mental Health Students on the Mental Health Continuum-Short Form (MHC-SF)

Abstract: Measures of positive well-being are needed to support the shift away from a deficit-based approach to mental health. This study examined one measure, the Mental Health Continuum-Short Form (MHC-SF), as a measure of positive well-being used in school-based mental health monitoring efforts. This study used latent profile analysis (LPA) to explore the mental health classifications of 10,880 California high school students’ responses to MHC-SF emotional, psychological, and social well-being items. Five latent ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(89 reference statements)
2
2
0
Order By: Relevance
“…As regards the convergent and discriminant validity of the SEDS-S, the results show that this scale correlates positively with the distress measure and negatively with well-being. This finding is consistent with previous studies reporting that the SEDS correlates significantly with instruments assessing anxious and depressive symptomatology and negatively with measures of emotional well-being, life satisfaction, socio-emotional skills, and HRQoL (Chan et al, 2022a , 2022b ; Dowdy et al, 2018 ; Furlong et al, 2020 , 2021 ; Maupin, 2021 ). These data are consistent with those of the SEDS-S-Brief, which provided validity evidence based on a relationship with measures of positive psychological states, such as well-being or life satisfaction (Dowdy et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As regards the convergent and discriminant validity of the SEDS-S, the results show that this scale correlates positively with the distress measure and negatively with well-being. This finding is consistent with previous studies reporting that the SEDS correlates significantly with instruments assessing anxious and depressive symptomatology and negatively with measures of emotional well-being, life satisfaction, socio-emotional skills, and HRQoL (Chan et al, 2022a , 2022b ; Dowdy et al, 2018 ; Furlong et al, 2020 , 2021 ; Maupin, 2021 ). These data are consistent with those of the SEDS-S-Brief, which provided validity evidence based on a relationship with measures of positive psychological states, such as well-being or life satisfaction (Dowdy et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding test-retest reliability, our study showed Cronbach's and McDonald's ω values between 0.86 and 0.89, which are slightly lower than those found in previous studies, but those studies only reported for the total sample, without differentiating according to gender (Chan et al, 2022a(Chan et al, , 2022bDowdy et al, 2018;Furlong et al, 2020Furlong et al, , 2021Kim et al, 2019;Maupin, 2021). These data are consistent with those of the SEDS-S-Brief (Dowdy et al, 2022), which supported reliability, although based on temporal stability.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All participants in their sample had a DSM‐5 ED diagnosis and, on this basis, were categorized as ‘high ED’. Thus, mental well‐being responses alone informed mental health status, which may misclassify individuals since this method does not account for differences in ED symptom severity or ‘moderate’ mental well‐being (Chan et al, 2021). In contrast, we used LPA which examined how mental well‐being and ED symptomatology varied together to identify mental health status.…”
Section: Discussionmentioning
confidence: 99%